A construção estética e cultural do crime em Coivara da Memória - Silva, Auda Ribeiro (2016)
This paper attempts to investigate the crime in the work of Coivara da Memória, or, so to speak, to analyze how the offense is built aesthetically and culturally in this novel. Consequently, the objective is to understand what the identity of the narrator-protagonist, his place, in short, how this narrative is structured. The discussion will be guided by the concept of "archive fever" (mal de arquivo) (Derrida), which is the breakdown of memory through the ambivalence of remembering and forgetting. This is because the narrator through the process reminiscent unbinds and archives the coivaras of his life and wants to write a book about himself in an attempt to atone for his own fault. We also use the concept of third space, as the voice of the narrator is a subject marginalized. To this end, the research presents itself in three chapters, the first is to focus the reception of the work of Francisco Dantas and his critical fortune, but also makes a presentation of the narrative plot in crime perspective, which is covered under the sociological and enigmatic bias. This study uses as theoretical support the concept of crime built from the reflections of Emile Durkheim (2001), Giddens (1989) and Michel Foucault (1987). The second concerns the narrator-protagonist, whose narrative is done according to his point of view, which now acts as a subject, now acts as the object of his memoirs, as it has in time an unclear boundary between past and present. For these and other reasons, this narrator is fragmented and contradictory, a frontier subject. These discussions were conducted by theorists Dal Farra (1973), Mieke Bal (1990), Bhabha (2007), Stuart Hall (2000), Bauman (2006). Finally, in the third chapter we emphasize the crime as archive fever, observing the discursive aspects and possible ambushes of the crime and the text as whole. For this discussion we use the terms "speech" by Michel Foucault (1996), and "archive fever" by Jacques Derrida (2001), among others.